Patients' perspective of attending nursing consultations-A pilot and feasibility study - Jytte Graarup; Ida Elisabeth Højskov (Wiley, 2020)
Abstract Aim The aims were to explore: (a) how patients with advanced heart and lung failure accept the overall framework of the nursing consultations and (b) the patients' acceptability and applicability of the nursing consultations. Design Qualitative study. Methods Interviews were conducted in an holistic frame and analysed using Graneheim and Lundman's qualitative content thematic analysis. Patients were interviewed between April and May 2018 regarding their general view of the nursing consultation and their experience of the framework inspired by R. R. Parse. Results The overall theme was A confidential moment with the nurse to deal with and become more aware of what is important, based on following subthemes: "An option that makes sense," "Scheduled time with the nurse is important" and "To find a new normality in everyday life." The framework addressed a space of freedom requested by the informants, for whom attending nursing consultations was useful and meaningful, enabling them to reflect on everyday challenges.